Sentiment Analysis Technology of Chinese Weibo under the Background of Big Data - Wang, Ruwei (Transactions on Social Science, Education and Humanities Research, 2023)
Chinese Weibo sentiment analysis technology is an important driving force for the development and progress of natural language processing, machine learning and other related fields. The purpose of this paper is to discuss the research of Chinese Weibo's sentiment analysis technology under the background of big data. At first, it summarizes the development history and current situation of sentiment analysis technology, then introduces the development status and challenges of Chinese Weibo's sentiment analysis technology, and finally looks forward to the future development of Chinese Weibo's sentiment analysis technology. At the same time, this paper deeply discusses the challenges faced by Chinese Weibo sentiment analysis technology, such as the processing of massive data, the processing of unstructured data, the complexity of sentiment understanding and the diversity of languages. In view of these challenges, this paper puts forward corresponding solutions and suggestions, and provides a useful reference for the development of Chinese Weibo sentiment analysis technology. Generally speaking, the emotional analysis of Chinese Weibo in this paper has important practical significance and application value, with a view to providing valuable theoretical support and practical guidance for the research and practice in related fields.